LEGAL STUDY OF THE RESPONSIBILITY OF FEMICIDE PERPETRATORS (STUDY OF DECISION NUMBER 333/PID.B/2022/PN SMG) - Simalango, Leonard Sarimonang (Jurnal Hukum Khaira Ummah, 2024)
This study aims to analyze future policies on the accountability of perpetrators of femicide in Indonesia; considerations of the panel of judges in sentencing perpetrators of femicide in Case Number 333/Pid.B/2022/PN Smg; and obstacles for the panel of judges in sentencing perpetrators of femicide in Case Number 333/Pid.B/2022/PN Smg and find solutions. This study uses a normative legal approach in the form of a conceptual approach, statute approach and comparative approach. The research data is in the form of primary, secondary and tertiary legal materials which are then analyzed qualitatively. Based on the study, it is concluded that (1) the regulation of future policies on the accountability of perpetrators of femicide in Indonesia is through regulations on the recognition of femicide as a special crime; regulations on increasing sentences for perpetrators of femicide; issuance of derivative regulations/implementing regulations; and strengthening collaboration with the TPKS Law and the PKDRT Law. (2) In sentencing the perpetrators of femicide in Case Number 333/Pid.B/2022/PN Smg, the panel of judges used legal, philosophical, and sociological considerations by considering aspects of retaliation, prevention, and justice. (3) The panel of judges in deciding on the criminal sentence for the perpetrators of femicide encountered obstacles in achieving a balance between justice and legal certainty as idealized in Radbruch's theory, so that the decisions taken were not fully in accordance with the moral, social, and legal demands expected. The solution to overcome these obstacles is the recognition of femicide in positive law in Indonesia; increasing access and quality of evidence by presenting expert sanctions in the field of gender-based violence; and developing responsive legal enforcement mechanisms.